FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELULUSAN MATA KULIAH ANATOMI MAHASISWA SEMESTER IV DI AKADEMI KEBIDANAN LATANSA MASHIRO RANGKASBITUNG TAHUN 2013 - Rita Rositawati (Akademi Kebidanan La Tansa Mashiro, 2014)
The data in the first semester to graduation anatomy courses only reached 51.5% in 2010, while in 2011 only reached 68%. The purpose of this study was to analyze the factors associated with student graduation anatomy courses. This type of research is the method of analytic type of case-control studies with a chi-square statistical test. The population in this research that all students in the fourth semester of the Academy of Midwifery La Tansa Mashiro Rangksbitung totaling 72 people. There was no significant association between parental support, faculty support, and learning atmosphere with graduation anatomy courses. There is a significant relationship between support classmates with graduation anatomy courses.